Understanding Generative AI Business Applications A Guide to Technical Principles and Real-World Applications - Cronin, Irena (Apress, 2024)
This guide covers the fundamental technical principles and various business applications of Generative AI for planning, developing, and evaluating AI-driven products. It equips you with the knowledge you need to harness the potential of Generative AI for enhancing business creativity and productivity. The book is organized into three sections: text-based, senses-based, and rationale-based. Each section provides an in-depth exploration of the specific methods and applications of Generative AI. In the text-based section, you will find detailed discussions on designing algorithms to automate and enhance written communication, including insights into the technical aspects of transformer-based Natural Language Processing (NLP) and chatbot architecture, such as GPT-4, Claude 2, Google Bard, and others. The senses-based section offers a glimpse into the algorithms and data structures that underpin visual, auditory, and multisensory experiences, including NeRF, 3D Gaussian Splatting,Stable Diffusion, AR and VR technologies, and more. The rationale-based section illuminates the decision-making capabilities of AI, with a focus on machine learning and data analytics techniques that empower applications such as simulation models, agents, and autonomous systems. In summary, this book serves as a guide for those seeking to navigate the dynamic landscape of Generative AI. Whether you're a seasoned AI professional or a business leader looking to harness the power of creative automation, these pages offer a roadmap to leverage Generative AI for your organization's success. What You Will L earn What are the technical elements that constitute the makeup of Generative AI products? What are the practical applications of Generative AI? How can algorithms be designed to automate and improve written communication? What are the latest Generative AI architectures and algorithms? Who This Book Is For Data scientists, data analysts, decision makers, and business executives interested in gaining an understanding of Generative AI products.
Includes index. - Transformers. - Description based on online resource; title from digital title page (viewed on June 12, 2024)
Keywords: Artificial intelligence; Business -- Data processing; Intelligence artificielle; Gestion; Informatique; artificial intelligence